Faktor-Faktor Pendorong Kualitas Audit Inspektorat dalam Pengawasan Keuangan Daerah - Andi Agus; Nurna Aziza; Fitrien Mulyusnita (Jurnal Bingkai Ekonomi (JBE), 2016)
This research was aimed to examine competency factor, independency factor, and objectivity factor influance on the quality of audit of inspectorate in local finances supervision. The data in this study was collected through questioner filled by all staffs of Inspectorate of Lebong Regency, Province of Bengkulu that involved actively in audit/ supervision. The method analysis used was multiple linear regressions with IBM SPSS analysis program. The research result shows that competency factor, independency factor, and objectivity factor that belong to the auditors of Inspectorat of Lebong Regency (Province of Bengkulu) were proven positively influence towards the quality of audit of Inspectorate of Lebong Regency in local finances supervision.